ANALISIS TREN PERTUMBUHAN EKONOMI BERBAGAI SEKTOR DI KABUPATEN TOBA SAMOSIR - Sihaloho, Henrykus (UNIKA Santo Thomas, 2014)
The goals of this research were to acquire overview of economic growth trend on several sectors and to identify the potency of the economic growth describing the conditions will be developed. Agriculture and industry was two main sector in forming Toba Samosir Regency’s Gross Regional Domestic Product (GRDP) at Current Market Prices 2009-2013 in 2013 and contributing over two third GDRP of Toba Samosir Regency. Although agricultural GRDP was increasing every year, but the contribution of this sector tend to decrease proportionally. There were three sector had location quotient’s score (LQ score over 1, namely agriculture, industry, and electricity, gas, and water sectors. This figure showed the economic growth acceleration was greater than the same sector in North Sumatera Province. LQ score’s agriculture at constant market prices in 2013 was almost twice than industry. It meant the potency of agriculture was almost twofold than industry.